2018
DOI: 10.1080/00913847.2018.1484658
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse tissue characterization of the anterior talofibular ligament: a promising noninvasive approach in ankle imaging

Abstract: ARFI seems to be a valuable diagnostic modality and represents a promising imaging marker for the assessment and monitoring of ankle ligaments in the context of acute and chronic ankle instabilities; ARFI could also be used to investigate loading or sport dependent adaptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The literature on USE for imaging ligaments is scarce. [64][65][66][67] Joint positioning plays an important role in ligament USE imaging because stretched ligament or relaxed ligament differ substantially. 64 Two articles studied healthy volunteers for the characterization of the anterior talofibular ligament and collateral ligament of the elbow.…”
Section: Ligamentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on USE for imaging ligaments is scarce. [64][65][66][67] Joint positioning plays an important role in ligament USE imaging because stretched ligament or relaxed ligament differ substantially. 64 Two articles studied healthy volunteers for the characterization of the anterior talofibular ligament and collateral ligament of the elbow.…”
Section: Ligamentsmentioning
confidence: 99%
“…64 Two articles studied healthy volunteers for the characterization of the anterior talofibular ligament and collateral ligament of the elbow. 65,66 Both concluded that USE could prove useful in evaluation of a ligament injury and in the follow-up of the healing process. 65,66 Gupta et al showed no significant differences in shear wave velocity between the dominant and nondominant arm when examining the ulnar collateral ligament.…”
Section: Ligamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all examinations, the Siemens S2000 ultrasound device (Acuson S2000, Siemens Healthineers, Erlangen, Germany) was chosen for data assessment. The system provides an ARFI based elastosonography option, which has revealed high reliability [14,17,18] and enables to compare conventional ultrasound imaging and ARFI quantification in one setting. To minimize pressure on the muscle tissue, a sufficient amount of ultrasound gel was applied between the skin and the transducer.…”
Section: Ultrasound Examinationmentioning
confidence: 99%
“…Acoustic radiation force impulse (ARFI) elastosonography has been established as a radiation-free method to obtain reliable tissue stiffness [13][14][15]. To our knowledge, there is no study demonstrating the consequences of CWI application on muscle stiffness via ARFI imaging.…”
Section: Introductionmentioning
confidence: 99%